DESIGNING AND IMPLEMENTING COSTUMER DATA INFORMATION SYSTEM OF SPEEDY SERVICES IN PLASA TELKOM SABANG - Fredy Wardhana; Fathiah Fathiah (JOURNAL OF INFORMATICS AND COMPUTER SCIENCE, 2017)
This system is designed for Direct Field Operational Control section (Teknik Oman) of Plasa Telkom Sabang. This system is able to store and easily search costumer data and present it in detail computationally. According to the result of analysis that had been conducted in the Teknik Oman section of Plasa Telkom Sabang, it can be concluded that this information system can facilitate the process of costumer data modification, like adding, editing, erasing, searching and printing all available costumer data. This will helps the officers efficiently solve various problems in the field and thus increases their performance. Keywords: SISKA Application, Teknik Oman, information system, waterfall model